Ligilactobacillus salivarius 7247 Strain: Probiotic Properties and Anti-Salmonella Effect with Prebiotics - Vyacheslav M. Abramov; Igor V. Kosarev; Andrey V. Machulin; Evgenia I. Deryusheva; Tatiana V. Priputnevich; Alexander N. Panin; Irina O. Chikileva; Tatiana N. Abashina; Ashot M. Manoyan; Anna A. Ahmetzyanova; Olga E. Ivanova; Tigran T. Papazyan; et al. (MDPI AG, 2023)
The Ligilactobacillus salivarius 7247 (LS7247) strain, originally isolated from a healthy woman's intestines and reproductive system, has been studied for its probiotic potential, particularly against Salmonella Enteritidis (SE) and Salmonella Typhimurium (ST) as well as its potential use in synbiotics. LS7247 showed high tolerance to gastric and intestinal stress and effectively adhered to human and animal enterocyte monolayers, essential for realizing its probiotic properties. LS7247 showed high anti-Salmonella activity. Additionally, the cell-free culture supernatant (CFS) of LS7247 exhibited anti-Salmonella activity, with a partial reduction upon neutralization with NaOH (p < 0.05), suggesting the presence of anti-Salmonella factors such as lactic acid (LA) and bacteriocins. LS7247 produced a high concentration of LA, reaching 124.0 ± 2.5 mM after 48 h of cultivation. Unique gene clusters in the genome of LS7247 contribute to the production of Enterolysin A and metalloendopeptidase. Notably, LS7247 carries a plasmid with a gene cluster identical to human intestinal strain L. salivarius UCC118, responsible for class IIb bacteriocin synthesis, and a gene cluster identical to porcine strain L. salivarius P1ACE3, responsible for nisin S synthesis. Co-cultivation of LS7247 with SE and ST pathogens reduced their viability by 1.0-1.5 log, attributed to cell wall damage and ATP leakage caused by the CFS. For the first time, the CFS of LS7247 has been shown to inhibit adhesion of SE and ST to human and animal enterocytes (p < 0.01). The combination of Actigen prebiotic and the CFS of LS7247 demonstrated a significant combined effect in inhibiting the adhesion of SE and ST to human and animal enterocytes (p < 0.001). These findings highlight the potential of using the LS7247 as a preventive strategy and employing probiotics and synbiotics to combat the prevalence of salmonellosis in animals and humans caused by multidrug resistant (MDR) strains of SE and ST pathogens.